The impact of boundary organizations on decision-making under uncertainty: A multi-agent simulation - Boissin, Denis (Applied Studies in Agribusiness and Commerce, 2009)
Modern environmental issues imply that decision-makers have the capacity to take into account possibly conflicting information from distinct domains, such as science and economics.As the development of technology increases the temporal and spatial scopes of risks, decision-makers can no longer consider economic and scientific information separately but should encourage experts to work together. Boundary organizations, institutions that cross the gap between two different domains, are able to act beyond the boundaries while remaining accountable to each side (Guston, 2001). By encouraging a flow of information across the boundaries, they permit an exchange to take place, while maintaining the authority of each domain (Cash et al., 2003; Clark et al., 2002). The goal is to simulate boundary organizations to assess their impact on the diffusion of experts’ opinions. The hypothesis tested is whether the existence of a boundary organization eases the decision-making process by reducing the number of opinions expressed. The methodology relies on a multi-agent system based on a model of continuous opinion dynamics (Deffuant et al., 2001) extended over two dimensions. The world is defined by two parameters: the uncertainty, that reflects the possible zone of discussion between experts, and the exchange, which represents the openness of discussions. Agents are described by credibility and conviction: the credibility represents how much other agents may be influenced by an agent, and the conviction represents the resistance of an agent to changing its position. Two kinds of agents are left free to interact, modifying their position in their domain (dimension) through one-to-one exchanges. Agents called borgs are introduced: open to trans-disciplinary discussion, they are able to exchange on both dimensions. The results show that the range of expressed opinions is significantly reduced, even at low levels of experts involved in the boundary organization.